Gender Politics and Social Class in Atwood’s Alias Grace Through a Lens of Pronominal Reference - Monacelli, Claudia (European Scientific Journal, ESJ, 2018)
In 1843, a 16-year-old Canadian housemaid named Grace Marks was tried for the murder of her employer and his mistress. The jury delivered a guilty verdict and the trial made headlines throughout the world. Nevertheless, opinion remained resolutely divided about Marks in terms of considering her a scorned woman who had taken out her rage on two, innocent victims, or an unwitting victim herself, implicated in a crime she was too young to understand. In 1996 Canadian author Margaret Atwood reconstructs Grace’s story in her novel Alias Grace. Our analysis probes the story of Grace Marks as it appears in the Canadian television miniseries Alias Grace, consisting of 6 episodes, directed by Mary Harron and based on Margaret Atwood’s novel, adapted by Sarah Polley. The series premiered on CBC on 25 September 2017 and also appeared on Netflix on 3 November 2017. We apply a qualitative (corpus-driven) and qualitative (discourse analytical) approach to examine pronominal reference for what it might reveal about the gender politics and social class in the language of the miniseries. Findings reveal pronouns ‘I’, ‘their’, and ‘he’ in episode 5 of the miniseries highly correlate with both the distinction of gender and social class. These patterns of repetition are indicative of the discourse structure of the TV miniseries Alias Grace.